Compliment Responses and Politeness in Canadian English - Bernard Mulo Farenkia (Progress in Language, Literature and Education Research Vol. 6, 2024)
This study focused on the intricate dynamics of face-enhancing strategies in responding to compliments. The research, conducted among English-speaking Canadian university students, challenges traditional patterns by revealing a notable inclination towards multifaceted responses. Unlike previous studies emphasizing the use of appreciation tokens in many English-speaking regions, participants in this study exhibited a unique trend of combining thanking with thoughtful comments. Also, the participants did not use negative compliment responses and they generally employed appreciation tokens in the construction of complex responses. The study contributes to research on speech acts in Canadian English and provides a starting point for comparison with other regional varieties of English and/or other languages.